Pattern of fungal isolates in cases of corneal ulcer in the western periphery of Nepal - Ganguly, S; Salma, KC; Sharma, M; Bastola, P; Pradhan, R (Nepalese Journal of Ophthalmology, 2011)
Purpose: To find out the epidemiologic features in 686 consecutive cases of fungal keratitis presenting in a tertiary eye hospital in the western region of Nepal. Materials and methods: A prospective hospital - based study was carried out on 1880 consecutive patients presenting with corneal ulcer in the outpatient department and cornea clinic of Lumbini Eye Institute, Bhairawa, Nepal. The socio-demographic data, predisposing risk factors, prior treatment modalities, laboratory results and the distribution pattern of fungus species were analyzed. Results: Diagnosis of fungus keratitis was established in 686 (36 %) out of the total study group of 1880 cases. The spectrum of fungi isolated were Fusarium species (Fusarium spp.) in 219 (31.9 %), followed by unidentified dematiaceous 151 (22 %), curvularia 122 (17.7 %) and unidentified hyaline in 111 cases (16.1 %). Men (59.3 %) were more commonly affected than women (40.6 %). The young adults age group of 31-40 years was most commonly involved (26.6 %). Corneal trauma (58 %) and topical steroids (12 %) were the most common predisposing risk factors noted. Conclusion: In contrast to the other studies done in Nepal, we found Fusarium to be the most common fungal isolate causing corneal ulcer followed by unidentified dematiaceous, unidentified hyaline and curvularia. Corneal trauma was the commonest predisposing risk factor in causing fungal keratitis. Keywords: cornea, fungal ulcer, fusarium, unidentified dematiaceous fungus DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5262 Nepal J Ophthalmol 2011; 3(2): 118-122